Establishing a compensation fund for victims of cyber fraud: Toward a legal framework for Qatar - Al-Eshaq, Noor Ahmed M H; Farag, Mohamed Salem Abou El; Kattan, Imad Abdulkarim (Edelweiss Applied Science and Technology, 2025)
The right of victims to receive compensation for harm caused by criminal acts is a fundamental legal principle recognized in many legal systems. With the widespread integration of modern technology into daily life, new forms of criminal activity—particularly cybercrimes—have emerged, including electronic fraud. These crimes present complex legal challenges, primarily due to the difficulty of identifying perpetrators and establishing civil liability when offenders often remain anonymous. Despite the efforts of authorities, prosecuting such crimes is frequently difficult, making it essential to explore alternative mechanisms for victim compensation. This study proposes the establishment of a dedicated compensation fund for victims of electronic fraud, financially supported by the state and private entities operating online. The fund would serve not as an admission of fault by these entities, but as a reflection of their duty to protect users and uphold social security. The research examines the legal basis, funding sources, eligible damages, and procedural requirements for such a fund, drawing attention to the gap in current Qatari legislation. While the Qatari Cybercrime Prevention Law No. 14 of 2014 criminalizes acts of electronic fraud, it does not provide a clear legal pathway for victim compensation when perpetrators are unknown. This article highlights the growing societal impact of electronic fraud, the legal vacuum surrounding victim compensation, and the need to develop responsive legal mechanisms. By addressing these issues, the study aims to contribute to the development of a fair and effective system that ensures victims of electronic fraud are not left without recourse.